Instrument for the evaluation of higher surgical training experience in the operating theatre. Issue 5 (7th May 2023) - Lau, K L; Scurrah, R; Cocks, H
Abstract: Objective: The operating theatre, as the primary learning environment for surgeons, needs to be conducive to achieve successful training. A validated 27-item questionnaire aimed at evaluating the training experience of higher surgical trainees in the operating theatre was developed. Methods: The initial questionnaire was developed using a literature review and a focus group. Items were validated with content validity index (CVI) and Cronbach's alpha. Results: The initial version of 33 questions was modified in the focus group into a 29-item 4-point Likert scale questionnaire covering 3 areas. Of these 29 items, 27 reached the threshold CVI of 0.87, and they achieved a Cronbach's alpha of 0.89 from 17 responses. Conclusion: The quantitative validations in the instrument are comparable to other existing medical education evaluation tools. Aspects of non-technical skills and human factors were featured heavily and perceived to be important for learning in the operating theatre.